Pengaruh renovasi terhadap makna rumah tradisional masyarakat Jawa, kasus studi: Kotagede Yogyakarta - Bonifasius Sumardiyanto (ARTEKS : Jurnal Teknik Arsitektur, 2019)
The meaning of traditional Javanese house is as an expression of respect to creating harmonious relations with the numinous unity of supernatural environment, natural environment, and community. This is done in order to achieve safety in the life of Javanese people. To accommodate the demands of development needs, especially from the economic aspect, some houses experienced renovations in the form of adding commercial functions to their initial residential functions. As a case study, four houses which have been renovated were chosen. This study sought to reveal the effect of the renovation on the meaning of the house. The research begins by identifying the zones of each houses before renovation. Then the zones of each room were identified as a result of the renovation. The next step was to identify the suitability of the space zone due to renovation of the initial zone. Based on the suitability or incompatibility of the zone, the structuralism approach was used to interpret the effect of renovation on the meaning of the house. The results show that the renovation of the traditional house generally only affects the change on surface structure and not on the deep structure, thus, does not change its meaning. The wider the original house and the more residents living there, the higher the possibility of changing the meaning. © 2019 Bonifasius Sumardiyanto